2017
DOI: 10.1177/1094670516685179
|View full text |Cite
|
Sign up to set email alerts
|

The Social Dimension of Service Interactions

Abstract: Service interactions run a gamut from an instrumental self-focus to full social appreciation. Observing another customer's incivility toward a frontline employee can emphasize social concerns as guiding principles for the observer's own service interaction. Five studies test these dynamics; the results reveal that an incivility incident leads observers to prioritize social over market concerns. This reprioritization becomes manifest in a subsequent service interaction through increased feelings of warmth towar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 94 publications
(33 citation statements)
references
References 85 publications
3
30
0
Order By: Relevance
“…Managers of thrift‐oriented brands need to be aware of the potential impact their positioning strategy has on their employees and identify means to offset the potential negative effects. For instance, these managers might consider supplementing their positioning with cues emphasizing the social dimension of consumption (Henkel, Boegershausen, Rafaeli, & Lemmink, ). In addition, personnel managers of thrift‐oriented brands can excel by proactively equipping their employees with the tools and internal culture to cope with potentially less considerate customers.…”
Section: Discussionmentioning
confidence: 99%
“…Managers of thrift‐oriented brands need to be aware of the potential impact their positioning strategy has on their employees and identify means to offset the potential negative effects. For instance, these managers might consider supplementing their positioning with cues emphasizing the social dimension of consumption (Henkel, Boegershausen, Rafaeli, & Lemmink, ). In addition, personnel managers of thrift‐oriented brands can excel by proactively equipping their employees with the tools and internal culture to cope with potentially less considerate customers.…”
Section: Discussionmentioning
confidence: 99%
“…Service incivility can take the form of rude, impolite, and condescending acts against employees (Henkel et al, 2017) or customers (Porath et al, 2011) during a service encounter. These behaviors could be either experienced or witnessed by customers (Karabas et al, 2019).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Empathic feelings of concern and compassion prompt a desire to reduce the distress or need of the other (Batson, 1991;Betancourt, 1990;Eisenberg et al, 2010), and motivate prosocial behaviors (Batson, 1991), such as interpersonal helping and positive social attitudes (Lebowitz & Dovidio, 2015). Indeed, Henkel et al (2017) found that witnessed incivility elicited feelings of warmth toward a frontline employee, which in turn related to prosocial feelings and emotional support (provided observers did not attribute blame to the employee). This desire to help is due to a backwards inference process in which individuals infer from their feelings of concern that they value that individual's welfare (Batson et al, 2007).…”
Section: Perspective-taking and Observer Empathetic Concernmentioning
confidence: 99%